2002
DOI: 10.1007/s00330-001-1269-y
|View full text |Cite|
|
Sign up to set email alerts
|

Screen film vs full-field digital mammography: image quality, detectability and characterization of lesions

Abstract: The objective of this study was to compare screen-film mammography (SFM) to full-field digital mammography (FFDM) regarding image quality as well as detectability and characterization of lesions using equivalent images of the same patient acquired with both systems. Two mammography units were used, one with a screen-film system (Senographe DMR) and the other with a digital detector (Senographe 2000D, both GEMS). Screen-film and digital mammograms were performed on 55 patients with cytologically or histological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
58
0
9

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(68 citation statements)
references
References 15 publications
0
58
0
9
Order By: Relevance
“…The acquired digital image can be stored in computer memory and printed out later as a fi lm or displayed and interpreted on a high-defi nition monitor. The ability to alter contrast and brightness permits further evaluation of abnormal areas to identify features diagnostic of benign and malignant disease [12][13][14] . Although the overall cancer-detection rate is similar in screen-fi eld and full-fi eld mammography, screenfi eld imaging has better image quality and fewer artefacts, and requires fewer patient recalls 14 .…”
Section: Mammographymentioning
confidence: 99%
“…The acquired digital image can be stored in computer memory and printed out later as a fi lm or displayed and interpreted on a high-defi nition monitor. The ability to alter contrast and brightness permits further evaluation of abnormal areas to identify features diagnostic of benign and malignant disease [12][13][14] . Although the overall cancer-detection rate is similar in screen-fi eld and full-fi eld mammography, screenfi eld imaging has better image quality and fewer artefacts, and requires fewer patient recalls 14 .…”
Section: Mammographymentioning
confidence: 99%
“…Acquisition with the appropriate exposure parameters can correct this [1,2]. The incidence of underexposure on the indirect type of FFDM has been reported to be 4 % and on the screen-film system 8 % [3]. In the present study, the incidence of underexposure on the direct and indirect types of FFDM was a significantly lower 0.7 %.…”
Section: Discussionmentioning
confidence: 41%
“…Only one previous study has examined FFDM artifact incidence: comparing artifacts of screen-film mammography with FFDM. It showed that artifacts occurred in 78 % of screen-film mammography cases, but not at all in FFDM [3]. Crystallization and blooming artifacts, manifesting as blurring of image corners and white dots within a black halo, have been reported for the selenium-based digital mammography detector; these were thought to be detector-hardware related [5].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Digital mammography has a lower spatial resolution than SFM, but has a very high contrast resolution. This allows the overall resolution of digital mammography to be at least equivalent to SFM [4][5][6][7][8], even when viewing calcification smaller than the pixel size [9]. Some CR systems have not met the quality standards of a number of governing bodies for mammography, including the European Network of Reference Assessment Centres (EUREF) and the NHS Breast Screening Programme (NHSBSP) [10,11].…”
mentioning
confidence: 99%